Evaluation of the efficacy of optimal pulsed technology treatment in patients with cataract and Meibomian gland dysfunction in the perioperative period - Jinling Ge (BMC Ophthalmology, 2020)
Abstract Background The aim of this study was to evaluate the efficacy and safety of M22 Optimal Pulsed Technology (OPT) applied in patients with age-related cataract and Meibomian gland dysfunction (MGD) in perioperative period. Methods This prospective observational study was carried out in the Jinan Mingshui Eye Hospital (Zhangqiu, China). We studied 60 patients (30 in the OPT treatment group and 30 in the conventional surgery group) with age-related cataract and MGD who underwent phacoemulsification and evaluated the efficacy of OPT treatment before and 1 month and 3 months after surgery. Ocular Surface Disease Index (OSDI) questionnaire, biomicroscopic examination of lid margins, Meibomian gland yielding secretion score (MGYSS), corneal fluorescein staining scores (CFS), tear film break-up time (TBUT), tear meniscus height (TMH) and the morphology of the MG (meibography) followed by Keratograph 5 M (K5M) were used to assess the patients’ conditions. Results There were significant differences in the scores of OSDI, MGYSS, TBUT, and CFS between the preoperative and postoperative outcomes (p < 0.05). In the OPT treatment group, the postoperative ocular surface condition was obviously better and the patient satisfaction rate was higher than those before surgery. There were significant differences in the scores of OSDI, EMAS, MGYSS and CFS before and 1 month after surgery (p < 0.05). In addition, there were also significant differences in the scores of OSDI, EMAS, MGYSS and MGLS before and 3 months after surgery (p < 0.05). No complications appeared during OPT treatment. Conclusions Cataract surgery can aggravate MGD and is detrimental to ocular surface health. OPT treatment was a safe and effective intervention for patients with MGD and cataract during perioperative period.